Perinatal stem cells - Murphy, Sean V.; Atala, Anthony (Springer New York, 2014)
This comprehensive volume is one of the first books to offer the reader detailed insight into sources of perinatal stem cells, their biology,  and their potential for disease treatment. It examines the research and therapeutic applications of perinatal stem cells including the treatment of renal disease, hematopoietic regeneration, cardiac disease, inflammatory disease, bone regeneration, pulmonary disease, and the treatment of spinal cord injury. Further, the book discusses current progress in the manufacturing, banking and clinical translation of perinatal stem cells. Through this book, readers will gain a thorough understanding of the current pre-clinical and clinical applications of perinatal stem cells as well as the efforts to support the transition of perinatal stem cell therapies from laboratories to clinics. Perinatal Stem Cells contains thirty-two chapters written by internationally recognized leaders in stem cell research. It is organized into four sections covering amniotic fluid stem cells, placental and placental membrane stem cells, umbilical cord stem cells, and clinical translation. This cohesive structure provides an effective framework for detailed insight into this new frontier. Edited by Dr. Anthony Atala, one of the foremost experts in the field, and his co-editor Dr. Sean V. Murphy, this volume is a definitive work for stem cell research and its future implications. It is a key resource for all stem cell researchers, clinicians, and government and industry staff working in this dynamic and exciting field.